The effect of black chokeberry (aronia melanocarpa) on human inflammation biomarkers and antioxidant enzymes: a systematic review of randomized controlled trials - Sarıkaya, Buse; Kolay, Ezgi; Güney Coşkun, Merve; Yiǧit Ziolkowski, Aslı; Aktaç, Şule (My University, 2025)
Context: Consuming antioxidant-rich foods has been associated with potential benefits in managing chronic diseases by reducing oxidative stress and inflammation. Objective: This systematic review aimed to evaluate the effects of Aronia melanocarpa (aronia berry or chokeberry) on human inflammation biomarkers and antioxidant enzymes. Data Sources: A systematic search was conducted across multiple databases, including PubMed, Scopus, Science Direct, and Web of Science, to identify relevant studies investigating the potential effects of aronia on human inflammation biomarkers and antioxidant enzymes between April 2022 and November 2023. Data Extraction: The selection of studies followed the PRISMA guidelines, data screening was conducted by 4 independent reviewers, and data extraction and risk-of-bias assessments were performed by 2 independent reviewers using the Cochrane Risk of Bias 2 tool. Data Analysis: A total of 1986 studies were screened, and 18 studies that met the inclusion criteria were included in a systematic review that investigated the anti-inflammatory effects of aronia on various health parameters. These studies primarily focused on the effects of aronia on cardiometabolic diseases, performance in sport, and other health parameters. Conclusions: This study examined the effects of Aronia intervention on human health outcomes using aronia juice, extract, or oven-dried powder for a period of 4 to 13 weeks. The primary health parameters considered were C-reactive protein (CRP), interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-α), interleukin-8 (IL-8), interleukin-10 (IL-10), interleukin-1β (IL-1β), superoxide dismutase (SOD), catalase (CAT), and reduced glutathione peroxidase (GSH-Px). The results showed that aronia had a beneficial effect on several inflammatory cytokines, including reductions in CRP, TNF-α and IL-6 concentrations, as well as elevated IL-10 levels. Moreover, positive changes have been observed in antioxidant enzyme systems, including; elevated SOD, GSH-Px and CAT activity. The findings of the presented studies provide evidence that Aronia melanocarpa may have beneficial effects on inflammatory markers. Systematic Review Registration: PROSPERO registration No. CRD42022325633.
Keywords: Antioxidants; Aronia Melanocarpa; Black Chokeberry; Inflammation